The influence of Kinesiology Taping on the reduction of lymphoedema among women after mastectomy – preliminary study - Pop, Teresa Bronisława; Karczmarek-Borowska, Bożenna; Tymczak, Monika; Hałas, Ireneusz; Banaś, Joanna (Contemporary Oncology/Współczesna Onkologia, 2014)
Introduction: Kinesiology Taping is a method that assists healing processes and improves the physical efficiency. The aim of the study was to assess the influence of Kinesiology Taping on the lymphoedema reduction among women after mastectomy. Material and methods : The subject of the research included 44 women underwent single mastectomy along with the removal of lymph nodes. The examination was carried out from the 4th of January to the 4th of February, 2013. The traditional taping method was implemented among 22 women, whereas the own taping method was used among the other 22 women. The therapy took 21 days, during which the tapes were applied three times every 7 days. The measurements were made before every application and at the end of the therapy. In the study, a questionnaire was used and it included questions concerning basic demographic, epidemiological data as well as the evaluation of the therapy effectiveness. The linear measurements of the upper limbs, the measurements of the range of joints’ motion in the upper limb were taken as well as grip strength was made. Results : The reduction of the volume of lymphoedema of 55% was reported in the study group, whereas the oedema reduced by 27% in the clinical control one. Conclusions : In the reduction of lymphoedema, the greater effectiveness of the own taping method in comparison to the traditional one was reported. Kinesiology Taping exerted an influence on the improvement of the upper limb’s joints movability and the grip strength.